Regional workshop on preparedness and response to aquatic animal hea lth emergencies in Asia : 21-23 September 2004, Jakarta, Indonesia - Regional Workshop on Preparedness and Response to Aquatic Animal Hea lth Emergencies (2004 : Jakarta, Indonesia); Subasinghe, R. P. (Rohana P.); Arthur, J. R. (James Richard), 1948-; Food and Agriculture Organization of the United Nations (Rome : Food and Agriculture Organization of the United Nations, 2005)
"The Regional Workshop on Preparedness and Response to Aquatic Anima l Health Emergencies focused on emergency planning and responses to ser ious outbreaks of aquatic animal diseases in Asia. These proceedings in clude all the papers presented, group reports and resulting recommendat ions. The workshop was organized jointly by FAO, the Network of Aquacul ture Centres in Asia-Pacific and the WorldFish Center and was hosted by the Government of Indonesia, Ministry of Marine Affairs and Fisheries. The material covers a wide range of topics, from a review of the histo ry, current status and socio-economic impacts of transboundary aquatic animal diseases in Asia to analyses of regional needs in areas such as contingency planning, legislation and capacity building."
Includes bibliographical references.
Keywords: Aquatic animals -- Diseases -- Asia -- Management -- Congresses; Fishes -- Diseases -- Asia -- Congresses; Aquaculture -- Asia -- Congresses; Fishes -- Conservation -- Asia -- Congresses